Patients Submitted to Myocardial Revascularization with the Use of Bilateral Internal Thoracic Arteries: Diabetics vs. Non-Diabetics - Abelaira Filho,Achilles (2021)
Abstract Introduction: Use of bilateral internal thoracic artery (BITA) as graft in coronary artery bypass grafting (CABG) is controversial because it is related to higher in-hospital mortality, incidence of sternal wound-related infection, and an increase in surgical time. The primary objective of this study is to evaluate in-hospital mortality and mortality within 30 days from discharge. The secondary objective is to evaluate the occurrence of deep sternal wound infection in a 90-day follow-up. Methods: This is a retrospective review of the medical records of 152 patients undergoing elective CABG with the use of BITA and cardiopulmonary bypass (CPB). These patients were divided into two groups, diabetics and non-diabetics. Patients with acute myocardial infarction and concomitant valvular disease were not included in the sample. Results: Preoperative characteristics did not show significant differences between the groups, which allowed a comparative analysis. The variables electrocardiography time and aortic clamping time were higher in the diabetic group, with a significant statistical difference (P<0.0001). In-hospital mortality occurred in three patients, and there was no mortality up to 30 days in both groups. There was no significant difference in the primary end point between groups (P=0.56). Deep sternal wound infection was present in only one patient and showed no significant difference in the secondary outcome between groups (P=0.40). Conclusion: We did not observe a higher mortality and occurrence of deep sternal wound infection with the use of BITA in diabetic patients compared to non-diabetics, even with greater CPB and aortic clamping times in diabetics.